2023
DOI: 10.3390/nu15081919
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of High Breastfeeding Self-Efficacy among Nursing Mothers in Najran, Saudi Arabia

Abstract: Many factors have been found to correlate with satisfactory Exclusive Breastfeeding (EBF) practices. The relationships between EBF practices and associated factors are complex and multidimensional; Breastfeeding Self-Efficacy (BSE) is the most important psychological factor that may help the mother to overcome any expected barriers. This study investigates the determinants of high breastfeeding self-efficacy among Saudi nursing mothers. Methods: This is a descriptive cross-sectional study investigating the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
1
1
1
Order By: Relevance
“…Another strength of this study is that it allows us to identify areas for improvement or gaps to target and focus interventions on, both for mothers and healthcare professionals, as well as the healthcare system. This is consistent with similar studies [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…Another strength of this study is that it allows us to identify areas for improvement or gaps to target and focus interventions on, both for mothers and healthcare professionals, as well as the healthcare system. This is consistent with similar studies [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, Hegazi et al reported that most of their study participants had good knowledge regarding BF except for colostrum and continuation [29]. Other Saudi studies also reported good BF knowledge [16,30]. Although the BF knowledge in the current study was to some extent lower than in the previously mentioned Saudi studies, it was still much higher than in some international studies [31,32].…”
Section: Discussioncontrasting
confidence: 58%
“…In addition, positive thoughts and attitudes about breastfeeding during pregnancy contribute to the development of confidence in breastfeeding and make it easier to overcome difficulties [40]. Similarly, in a different study, possessing sufficient knowledge about breastfeeding and having positive attitudes toward breastfeeding were positively correlated with increased levels of breastfeeding self-efficacy [41]. In our study, approximately 30.0% of the mothers had insufficient knowledge about breastfeeding, indicating the need for informative sessions about breastfeeding as part of prenatal care programs.…”
Section: Discussionmentioning
confidence: 91%